The severed land - Gee, Maurice 1931- (Puffin, Penguin Random House New Zealand, 2017)
"From the high reaches of a tree, Fliss watches the soldiers attempting yet again to break through the invisible wall. Amid the explosions, a drummer boy tries to escape. As he is about to be shot, Fliss reaches through the wall and pulls him to safety. But Fliss is dismayed to find she has saved an overfed rich boy. She is even more dismayed to learn that she must accompany him back through the wall on a special mission to rescue the Nightingale. The world they have to travel through is a perilous one, full of predatory thieves, slave masters, beggars, dippers, mudlarks, drain-sliders, spies and wall-men. It is a world where the ruling families are caught up in a lethal power struggle. Will Fliss and the despised drummer boy learn to trust each other? Who is the Nightingale? And will they all make it back alive?"--Publisher information
National Library of New Zealand Cataloguing in Publication (CiP) record
Novel for young adults
Keywords: Fantasy; Fantasy fiction; Fiction; Young adult works; Young adult fiction, New Zealand; Young adult fiction; Jugendbuch